Chitosan-Based Nanospheres as Drug Delivery System for Cytarabine - S.SANGEETHA,; HARISH.G,; MALAY.K.SAMANTA, (International Journal of Pharma and Bio Sciences, 2010)
Nanoparticle made up of biodegradable carrier such as chitosan have advantage of providing stearic interference in the systemic circulation. Cytarabine nanospheres were prepared by ionic gelation method with an objective of improving its intracellular targeting and thereby targeting the cancer cells. The average particle size determined through SEM was found to be 466.45 ± 5.32 nm. The average drug loading was found to be 62% for the batch loaded with 1.50 mg/ml of drug when compared to other batches. The cumulative percentage of drug release from all the drug loaded batches at 18 hours was found to be in the range of 86.73 % to 93.50%.Among the four batches of nanoparticles formulated the batch containing 1.50mg of drug/ml of polymer showed the highest of about 93.50% of release. Release of drug from the matrix was by non-Fickian analomous diffusion mechanism. Invivo bio distribution studies showed that the Cytarabine in the form of nanoparticles was having a greater bio distribution when compared to free drug in different organs like liver, spleen, lungs and kidney.